Characterization of bonding modes in metal complexes through electron density cross‐sections. Issue 32 (21st September 2020) - de Beer, Shane; Cukrowski, Ignacy; de Lange, Jurgens H.
Abstract: Qualitative inspection of molecular orbitals (MOs) remains one of the most popular analysis tools used to describe the electronic structure and bonding properties of transition metal complexes. In symmetric coordination complexes, the use of group theory and the symmetry‐adapted linear combination (SALC) of fragment orbitals allows for a very accurate and informative interpretation of MOs, but the same procedure cannot be performed for asymmetric complexes, such as Schrock and Fischer carbenes. In this work, we present a straight‐forward approach for classifying and quantifying MO contributions to a particular metal–ligand interaction. Our approach utilizes the topology of MO density contributions to a cross‐section of an inter‐nuclear region, and is computationally inexpensive and applicable to symmetric and asymmetric complexes alike. We also apply the same approach with similar decompositions using Natural Bond Orbitals (NBO) and the recently developed Fragment, Atomic, Localized, Delocalized and Interatomic (FALDI) density decomposition scheme. In particular, FALDI analysis provides additional insights regarding the multi‐centric nature of metal‐carbene bonds without resorting to expensive multi‐reference calculations. Abstract : A method is presented by which the relative contributions of components of CMO, NBO or FALDI density is quantified along a λ ‐eigenvector of the Hessian matrix. The density (orbital or electron) is integrated along the eigenvector and normalized to obtain the contributions of each component to the overall interaction. It is then possible to identify specific orbitals or electron density components which have a greater impact on the nature of the interaction.